2019
DOI: 10.1128/aac.02157-18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Characteristics of qacA - and qacB -Positive Methicillin-Resistant Staphylococcus aureus Causing Bloodstream Infections

Abstract: The increasing use of chlorhexidine for methicillin-resistant Staphylococcus aureus (MRSA) decolonization has raised concerns about the emergence of resistance to these agents. However, the clinical significance of MRSA positive for the qacA and qacB chlorhexidine tolerance genes has not been established. We investigated the clinical features and predictive factors of MRSA bloodstream infection (BSI) isolates, caused by qacA-and qacB-positive MRSA, from 2010 to 2016 at a tertiary hospital in South Korea. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…Interestingly, the t2460 spa type has been identified mostly in Asia (24)(25)(26), and t2460 isolates reported from China carried qacA or qacB genes (22,27). In South Korea, both t2460 and t9353 are the major spa types of MRSA (28)(29)(30), and t2460 was reported to be associated with qacA or qacB genes (29). In addition, there was an increase in the proportion of low-level mupirocin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the t2460 spa type has been identified mostly in Asia (24)(25)(26), and t2460 isolates reported from China carried qacA or qacB genes (22,27). In South Korea, both t2460 and t9353 are the major spa types of MRSA (28)(29)(30), and t2460 was reported to be associated with qacA or qacB genes (29). In addition, there was an increase in the proportion of low-level mupirocin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that clinical S. aureus isolates carrying the qacA and qacB QAC resistance genes require an increased minimum inhibitory concentration of chlorhexidine and display increased resistance to β-lactam antibiotics [112]. These pumps are a common effective means of increasing cell tolerance to antimicrobial substances [52, 76].…”
Section: Bacterial Responses To Stimulimentioning
confidence: 99%
“…The Gram-positive QacA efflux pump family is activated by a broad range of antimicrobial agents (such as QAC-containing compounds), and is capable of extruding a wide variety of cationic substances from the cell cytoplasm [37]. It has been found that clinical S. aureus isolates carrying the qacA and qacB QAC resistance genes require an increased minimum inhibitory concentration of chlorhexidine and display increased resistance to β-lactam antibiotics [112]. These pumps are a common effective means of increasing cell tolerance to antimicrobial substances [52,76].…”
Section: Consequences Of Bacterial Adaptive Pathwaysmentioning
confidence: 99%
“…The QacA/B, NorA, and Smr multidrug efflux proteins are present on the S. aureus cell membrane [ 29 , 30 ]. MRSA harboring qacA and qacB genes has been found to be associated with increased resistance to non-β-lactam antibiotics and chlorhexidine tolerance [ 31 ].…”
Section: Antimicrobial Resistance In S Aureusmentioning
confidence: 99%